Investment Decision Analysis of Islamic Bank Listing Indonesia Stock Exchange Through Stock Price Valuation - Yudha Pratama, Versiandika; Difa, Farah; Achmad, Dliyaudin (Velocity: Journal of Sharia Finance and Banking, 2024)
This study aims to determine the intrinsic value (fair price) of Islamic bank stocks listed on the Indonesia Stock Exchange using a relative valuation approach which is then analyzed using two choices of methods, namely the price earning ratio (PER) method or the price to book value (PBV) method. The results of the valuation analysis are then used as guidelines for making investment decisions. This research belongs to the type of descriptive quantitative research with the type of data used is secondary data in the form of historical Islamic bank stock price data for the last 5 years, earning per share (EPS) data, and current book value per share (current BVPS) data, as well as data on the average PER value and the average PBV value of Islamic banks. The results show that BRIS and BTPS stocks valued using the PER method show that bank stocks are undervalued and worth buying. BANK and PNBS shares are valued using PBV because they have negative earnings. The results of the PBV method valuation on the two banks show that BANK and PNBS are classified as undervalued stocks and worth buying.